Unraveling the Role of RNA Mediated Toxicity of C9orf72 Repeats in C9-FTD/ALS - Kumar, Vijay; Hasan, Gulam M.; Hassan, Md. Imtaiyaz (Frontiers in Neuroscience, 2017)
The most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is intronic hexanucleotide (G4C2) repeat expansions (HRE) in the C9orf72 gene. The non-exclusive pathogenic mechanisms by which C9orf72 repeat expansions contribute to these neurological disorders include loss of C9orf72 function and gain-of-function determined by toxic RNA molecules and dipeptides repeats protein toxicity. The expanded repeats are transcribed bidirectionally and forms RNA foci in the central nervous system, and sequester key RNA-binding proteins (RBPs) leading to impairment in RNA processing events. Many studies report widespread transcriptome changes in ALS carrying a C9orf72 repeat expansion. Here we review the contribution of RNA foci interaction with RBPs as well as transcriptome changes involved in the pathogenesis of C9orf72- associated FTD/ALS. These informations are essential to elucidate the pathology and therapeutic intervention of ALS and/or FTD.